Effect of Inulin and Fermented Feed Additive on Growth and Nitrogen Balance in Pig - Wang, Weishan (2005)
Three experiments were conducted to determine the dietary crude protein (CP) level, inulin, and local available fermented feed additive (FFA) on growth, nitrogen (N) balance and fecal characteristics in growing pigs. Experiment 1 studied the fecal microflora fermentation using inulin compared with CMC in vitro. Gas volume, total volatile fatty acids (VFA) and purine bases (PB) concentrations of inulin fermentation were higher (P<O. 05) than the CMC. Experiment 2 investigated the dietary CP level and addition of inulin on growth, nitrogen balance and fecal characteristics in growing pigs. Twenty-four crossbred barrows (Duroc x Large white x Landrace) of an average body weight of 40 kg were used to conduct a 28-day experiment. The diet treatments were two levels of CP, 18% and 14% with or without 0.3% inulin addition. Daily live weight gain (DLWG) and feed conversion ratio (FCR) were not affected (P>0.05) by the dietary treatments. However, N intake and N excretion were decreased (P<0.05) with reduced CP level. Addition of inulin without further effect on the total amount of N excretion, but tended to shift N excretion from urine to feces. Higher (P<0.05) lactic acid bacteria (LAB) and lower (P<O.05) Enterobacteriaceae counts in feces for pigs fed with 14% CP and 14% CP + 0.3% inulin were observed. The hypothesis that addition of inulin and FFA would affect gastrointestinal (GIT) microorganisms, hence to improve N utilization was validated in Experiment 3. Twenty-four crossbred barrows (Duroc x Large White x Landrace) of an average body weight 65 kg were used in the 28-day experiment. Dietary treatments were addition of0.3% inulin (IN), 4% fermented feed additive (FFA), or their combination (IN + FFA). Pigs fed with IN + FFA had a higher (P<O.05) DLWG and a lower (P<0.05) FCR compared with other treatment groups. The quantity of total N excretion was not significantly (P>O.05) different among treatment groups, however, N excretion pattern tended to shift from urinary N excretion to fecal N excretion (P>O.05). Higher (P<O.05) LAB and lower (P<O.05) Enterobacteriaceae counts in feces for pigs fed with IN, FFA and IN + FFA compared to the pigs fed control diet were observed. It is concluded that inulin is readily fermented by GIT microbes. The inclusion of inulin or fermented feed additive, or both in the diets cannot reduce total N excretion but they can shift N excretion from urine to feces in growing pigs. N excretion can be decreased by reducing dietary protein from 18% to 14% without affecting the DLWG and FeR of growing pigs. The addition of inulin with fermented feed additive in the diet can improve DLWG and FCR. Reducing dietary CP level, inclusion of inulin or fermented feed additive, or both in the diets can modify GIT microorganism toward to a beneficially balance. In summary, inulin and fermented feed additive inclusion, along with the manipulation of dietary protein levels in pig diet, is a viable avenue to reduce nitrogen excretion in growing pigs.